Pengaruh Pemberian Promosi Kesehatan melalui Media Leaflet terhadap Pengetahuan Siswa/I tentang Pencegah Pencegahan TB Paru di SDN Sungai Lulut 8 Banjarmasin - Yusserliyawati Yusserliyawati; Ermeisi Er Unja; Margareta Martini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Tuberculosis is an infectious disease caused by the Mycobacterium Tuberculosis germ, which mostly attacks the lungs. The problem of controlling pulmonary tuberculosis has been implemented in many countries since 1995, but it remains a health problem in the community that causes high mortality among infants, children, adolescents, and seniors. One of the government programs in controlling pulmonary tuberculosis is the Joint Movement against tuberculosis in education units, the targets in the program are students, teachers, and education personnel from kindergarten to senior high school by providing health promotion. Data collection conducted by researchers found a health center with the highest incidence of pulmonary TB in children in Banjarmasin city, there is one elementary school closest to the health center. This study aims to provide health promotion through leaflet media on students' knowledge about the prevention of pulmonary tuberculosis at SDN Sungai Lulut 8 Banjarmasin. This study used quantitative research Pre-experimental method with a one group pretest-posttest approach. The population in this study were 199 people. The sampling technique used was purposive sampling with a sample size of 67 students. This research instrument uses a questionnaire. The statistical test used is the Wilcoxon signed rank test. The results show that there is a difference between before and after giving promotion.